The Olfactory Strip and Its Preservation in Endoscopic Pituitary Surgery Maintains Smell and Sinonasal Function - Harvey, Richard J.; Winder, Mark; Davidson, Andrew; Steel, Tim; Nalavenkata, Sunny; Mrad, Nadine; Bokhari, Ali; Barham, Henry; Knisely, Anna (Journal of Neurological Surgery Part B: Skull Base, 2015)
Background The return of olfaction and of sinonasal function are important end points after pituitary surgery. Opinions differ on the impact of surgery because techniques vary greatly. A modified preservation of the so-called olfactory strip is described that utilizes a small nasoseptal flap and wide exposure.Methods A cohort of patients undergoing pituitary surgery and endoscopic sinonasal tumor surgery were assessed. Patient-reported outcomes (Sino-Nasal Outcome Test [SNOT22] and Nasal Symptom Score [NSS]) were recorded. A global score of sinonasal function and the impact on smell and taste were obtained. Objective smell discrimination testing was performed in the pituitary group with the Smell Identification Test. Outcomes were assessed at baseline and at 6 months.Results Ninety-eight patients, n = 40 pituitary (50.95 ± 15.31 years; 47.5% female) and n = 58 tumor (52.35 ± 18.51 years; 52.5% female) were assessed. For pituitary patients, NSSs were not significantly different pre- and postsurgery (2.75 ± 3.40 versus 3.05 ± 3.03; p = 0.53). SNOT22 scores improved postsurgery (1.02 ± 0.80 versus 0.83 ± 0.70; p = 0.046). Objective smell discrimination scores between baseline and 6 months were similar (31.63 ± 3.49 versus 31.35 ± 4.61; p = 0.68). No difference in change of olfaction was seen compared with controls (Kendall tau-b p = 0.46).Conclusions Preservation of the olfactory strip can provide a low morbidity approach without adversely affecting olfaction and maintaining reconstruction options.
Keywords: smell; olfaction; nasoseptal; endoscopic; endonasal; pituitary